JAK inhibition ameliorates bone destruction by simultaneously targeting mature osteoclasts and their precursors - Shinya Yari; Junichi Kikuta; Hotaka Shigyo; Yu Miyamoto; Daisuke Okuzaki; Yuki Furusawa; Masafumi Minoshima; Kazuya Kikuchi; Masaru Ishii (BMC, 2023)
Abstract Background Rheumatoid arthritis (RA) is characterized by chronic inflammation and resultant cartilage/bone destruction because of aberrantly activated osteoclasts. Recently, novel treatments with several Janus kinase (JAK) inhibitors have been shown to successfully ameliorate arthritis-related inflammation and bone erosion, although their mechanisms of action for limiting bone destruction remain unclear. Here, we examined the effects of a JAK inhibitor on mature osteoclasts and their precursors by intravital multiphoton imaging. Methods Inflammatory bone destruction was induced by local injection of lipopolysaccharides into transgenic mice carrying reporters for mature osteoclasts or their precursors. Mice were treated with the JAK inhibitor, ABT-317, which selectively inhibits the activation of JAK1, and then subjected to intravital imaging with multiphoton microscopy. We also used RNA sequencing (RNA-Seq) analysis to investigate the molecular mechanism underlying the effects of the JAK inhibitor on osteoclasts. Results The JAK inhibitor, ABT-317, suppressed bone resorption by blocking the function of mature osteoclasts and by targeting the migratory behaviors of osteoclast precursors to the bone surface. Further exhaustive RNA-Seq analysis demonstrated that Ccr1 expression on osteoclast precursors was suppressed in the JAK inhibitor-treated mice; the CCR1 antagonist, J-113863, altered the migratory behaviors of osteoclast precursors, which led to the inhibition of bone destruction under inflammatory conditions. Conclusions This is the first study to determine the pharmacological actions by which a JAK inhibitor blocks bone destruction under inflammatory conditions; this inhibition is beneficial because of its dual effects on both mature osteoclasts and immature osteoclast precursors.